POTENTIAL ANALYSIS AND DEVELOPMENT STRATEGY OF CATTLE-PALM INTEGRATION LIVESTOCK BUSINESS IN OGAN KOMERING ULU REGENCY - Lily Meliana; Rini Efrianti; Yetty Oktarina; Fifian, Fifian Permata Sari (International Journal of Social Science, 2022)
The integration system between oil palm plantations and cattle must be supported by the application of appropriate and targeted technology, so that the resulting production can be more efficient, competitive and sustainable. The formulation of the problem in this research is how is the potential for the development of integrated cattle-palm farming business in Ogan Komering Ulu Regency. The method in this study used the survey method. The data collection method is an exploratory qualitative data collection method. The data analysis technique used is Location Quotient (LQ) analysis, Shift-Share analysis and SWOT analysis. The results of the study found that the cattle-oil integration farming business in Ogan Komering Ulu Regency could be developed using strengths using existing opportunities and this is a very profitable situation where Ogan Komering Ulu Regency has a cattle-oil integration livestock farming business with take advantage of existing opportunities. The strategy that can be used is the SO Strategy, namely (Strength and Opportunities), which is a strategy that optimizes strengths to take advantage of opportunities (opportunities), namely conducting counseling and coaching to farmer group farmers, providing counseling to farmers that cattle-palm integration can be a main source of income, utilization of cow dung as palm oil fertilizer and empowerment of existing cattle farmer groups to be able to partner with government and private institutions.